2022
DOI: 10.29303/jpm.v17i4.3629
|View full text |Cite
|
Sign up to set email alerts
|

The effect of essential oil concentrations on particle size of kencur (Kaempferia galanga L.) nanoemulsions with maltodextrin and tween 80 as emulgators

Abstract: Kencur (Kaempferia galanga L.) essential oil nanoemulsion was proposed to replace baby powder which has been banned in several countries. This study aimed to determine the effect of various kencur essential oil concentrations on particle size and to measure their stability during storage. This research was initiated by examining essential oil quality and followed by the formulation of nanoemulsion with maltodextrin and tween 80. PSA characterized it, and stability was observed for six weeks. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The downward regression direction indicates that the higher the concentration of the added extract, the lower the pH of the hand sanitizer gel. The pH value of hand sanitizer gel decreases due to the presence of flavonoid compounds in acidic extracts [16]. In addition, there is a fermentation treatment on the skin of Ari, which produces lactic acid bacteria that produce organic acids so that the pH value decreases [17].…”
Section: Figure 5 the Effect Of Fermented Extract Concentration Of So...mentioning
confidence: 99%
“…The downward regression direction indicates that the higher the concentration of the added extract, the lower the pH of the hand sanitizer gel. The pH value of hand sanitizer gel decreases due to the presence of flavonoid compounds in acidic extracts [16]. In addition, there is a fermentation treatment on the skin of Ari, which produces lactic acid bacteria that produce organic acids so that the pH value decreases [17].…”
Section: Figure 5 the Effect Of Fermented Extract Concentration Of So...mentioning
confidence: 99%
“…Pumival et al have reported that Tween 80 alone can stabilize a microemulsion of Citrus hystrix leaf oil [ 13 , 14 ]. Setyawati et al utilized Tween 80 as a surfactant to formulate a stable emulsion containing K. galanga rhizome oil [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kundun et al reported a nanoemulsion of K. galanga rhizome oil (0.4 mg/mL) prepared via an ultrasonication method using 1% saponin as a surfactant [ 19 ]. In another study, a nanoemulsion of K. galanga rhizome oil was prepared via ultrasonication using maltodextrin as a stabilizer and Tween 80 as a surfactant [ 18 ]. Praseptiangga et al prepared an edible film incorporated with Ceiba pentandra honey and K. galanga oil [ 20 ].…”
Section: Introductionmentioning
confidence: 99%